(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2025)
This study comes to understand the reflections of both social and cultural capital to the scientific formation among doctoral students; the research applies a qualitative approach by semi-structured interviews with 15 students. The study found a series of findings; it is observed that families with lower educational backgrounds possess moral cultural capital, while families with higher educational backgrounds possess both moral and material cultural capital, especially in the early stages of their educational journey. This support in their academic formation reflects on their scholarly capital. The first social group of students strives to elevate their academic standing to match the level of the second social group, characterized by high cultural capital and proficiency in research skills within the academic field regarding their social capital, the two groups demonstrate a broader network of social relationships compared to their virtual ones Keywords: Social Capital, Cultural Capital, scientific Formation, Doctoral Student, University